Berardi, Franco ‘Bifo.’ Heroes: Mass Murder and Suicide. London: Verso, 2015. 224 pp. ISBN: 9781781685785. £10.99. (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2018)
Berardi’s Heroes (2015) analyses the intricate relationship between capitalism and mental health by exploring the proliferation of mass murder and suicide in the twentieth-first century. This book is not essential to achieve a better understanding of Berardi’s theoretical edifice as a philosopher. Instead, Heroes offers a great application of his theoretical concepts on contemporary events, exhibiting how philosophy can be applied to contingent historical issues such as the ones dealt with in the book.